Refugees and Resources: Rethinking New England Humanitarianism as Global Affirmative Action - Goldstein, Emily S. (Tufts Archival Research Center, 2020)
I have been researching New England based humanitarian organizations that serve Muslim and or Middle Eastern refugees. I examine how these organizations practice humanitarianism in a way that centralizes the reallocation of resources and opportunities from the privileged to refugees. I argue that these examples can help frame humanitarianism as a system of global affirmative action that reckons with histories of global inequality and undermines the hegemonic humanitarian power dynamics between the philanthropists and the ‘needy.’ I cover the structuring of humanitarian organizations and their operations, the impact of institutionalized Islamophobia in U.S. politics, and a programming example of educational initiatives.